Detection of bovine Deltapapillomavirus DNA in peripheral blood of healthy sheep (Ovis aries). Issue 3 (12th January 2018) - Roperto, S.; Russo, V.; Corrado, F.; Munday, J. S.; De Falco, F.; Roperto, F.
Summary: Blood samples from 65 sheep were tested for the presence of bovine Deltapapillomavirus (δPVs) DNA. The sheep were divided into three groups. Sheep in groups 1 and 2 were from Sardinia and Campania, respectively, and were in contact with cattle and grazed on lands contaminated with bracken fern. Sheep in Group 3 lived in closed pens and had no contact with cattle. These sheep were fed hay that did not contain bracken fern. Bovine δPV E5 DNA was detected in blood from 24 of 27 (89%) sheep in Group 1. A single bovine δPV type was detected in the blood from nine (33%) sheep, including the detection of bovine δPV‐1 DNA in four sheep, bovine δPV‐2 in four and δPV‐13 in one sheep. Two δPV types were detected in 33% of the sheep, and three bovine δPV types were detected in 22% of the sheep. Bovine δPVs were detected in 17 of 20 (85%) sheep from Group 2. The detection rate by a single δPV type was 40% with just δPV‐1 DNA amplified from two, just δPV‐2 DNA from four, and just δPV‐13 DNA from two sheep. Two and three δPVs were detected in 30% and 15%, respectively. All sequenced amplicons showed a 100% identity with papillomaviral E5 DNA deposited in GenBank. Bovine δPV‐14 DNA sequences were not detected from any sheep. No bovine δPV DNA was revealed in blood samples from sheep in Group 3. The detection of bovine δPV DNA in the blood of sheep means that sheep may be able to be infected by these PVs. This suggests that bovine δPVs could potentially be a previously unrecognized cause of disease in sheep. Furthermore, it is possible that sheep could act as a reservoir for these viruses.